The association between adverse pregnancy outcomes with genital Chlamydia Trachomatis infection among pre-pregnancy couples in Shenzhen, China: A cross-sectional study - Sun, Si; Zhang, Li; Wu, Qiuhong; Tian, Lishan; Ding, Yi; Liu, Lanlan; Ye, Hailing; Li, Bo; Luo, Zhenzhou (Frontiers in Public Health, 2022)
Objectives: To investigate the prevalence of adverse pregnancy outcomes (APOs) in women and the impact of pre-pregnancy couples' genital Chlamydia Trachomatis (GCT) infection and other infections on APOs. Study design: Data on genital infections were collected from the Free Pre-pregnancy Health Check (FPHC) in Shenzhen, China. Data on APOs were collected from a one-year telephone follow-up of pregnancy status and subsequent pregnancy outcomes. Methods: APO data were used to count adverse outcomes, and logistic regression was conducted to determine the association between APOs and GCT infection. Results: From December 2018 to December 2019, among 4,429 couples who underwent FPHC; 1,925 were pregnant, and 1,816 couples were tracked for pregnancy outcomes, including 1,471 normal pregnancies and 345 (19.00%) APOs. The rest of 109 pregnant couples did not answer the phone or refused to answer the pregnancy outcome during the follow-up. Among APOs, the number of spontaneous abortions was 122 (35.36%), the number of macrosomia was 85 (24.64%), the number of low birth weight (LBW) & preterm births (PTB) was 39 (11.30%), the number of LBW was 34 (9.86%), and the number of PTB was 31 (8.99%). The prevalence of GCT infection in females and males was 4.24% (95% Confidence Interval, CI: 3.41% - 5.27%) and 3.58% (95% CI: 2.79% - 4.57%), respectively. More than half (52.69%, 49/93) of the couples were GCT-concordant. The prevalence of APOs in couples without GCT infection was 18.74% (332/1772). The prevalence of APOs in female GCT-discordant was 32.14% (9/28), and the prevalence of APOs in male GCT-discordant was 25% (4/16). The prevalence of APOs in GCT-concordant was 12.24% (6/49). Multivariable analysis indicated that females 30-35 years old (adjusted Odds Ratio (aOR) = 1.08, 95%CI: 1.01–1.17) and over 35 years old (aOR = 1.16, 95%CI: 1.03–1.32) were more likely to experiencing APOs. Conclusions: Although only women’s age was found to be associated with APOs, the prevalence of APOs with GCT-discordant in couples, especially female GCT-discordant, was higher than in those without infection or who were GCT-concordant, suggesting that these groups, especially in older women, should be paid more attention to in follow-ups to improve reproductive health.